The role of clinical history in the interpretation of chest radiographs. Issue 2 (May 2021) - Small, L.
Abstract: Objective: This review will appraise the literature pertaining to the influences that clinical history has on the action of assessing the chest radiograph. Key findings: There remains conflicting evidence on the impact of clinical history on chest radiography. Some research suggests that clinical history has the potential to influence the reporter in a negative way by limiting their search strategy to a more focussed search. Image interpretation is more accurate when reporters are allowed to conduct a free search of the chest image, untainted by preconceived concepts. Conclusion: Clinical history needs to be accessed appropriately to aid and not stifle accurate image interpretation. Reporters need to be aware of the potential bias clinical history can introduce to their reporting and develop strategies to alleviate this as much as possible. Implications for practice: A greater understanding of the potential bias of clinical history on the process of image interpretation is required by all reporters. Reporters need to develop an approach and strategy when accessing clinical history. Novice reporters need to be educated regarding the impact of clinical history on their reporting.